SPE Annual Technical Conference and Exhibition 2009
DOI: 10.2118/124946-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Level Mechanics of Forced and Spontaneous Imbibition of Aqueous Surfactant Solutions in Fractured Porous Media

Abstract: Water flooding typically recovers about 50% of the original oil in place leaving much oil in the reservoir. Recovery efficiency in fractured reservoirs can be dramatically lower in comparison to conventional reservoirs because water channels selectively from injector to producer leaving considerable oil within the matrix and uncontacted by injected water. An enhanced recovery process is needed to access such oil held in the reservoir matrix. Addition of aqueous surfactants to injection water dramatically reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Gautam et al demonstrated an imbibition model with the presence of fracture fluid flow using the droplet detachment model [19]. Most of the past research concerning the analytical or numerical model of imbibition is based on the nonlinear diffusion equation [20,21,22,23,24]. The numerical model of imbibition considering the effects of surfactant, which are wettability alteration and IFT, were also established [25,26].…”
Section: Cos Cmentioning
confidence: 99%
“…Gautam et al demonstrated an imbibition model with the presence of fracture fluid flow using the droplet detachment model [19]. Most of the past research concerning the analytical or numerical model of imbibition is based on the nonlinear diffusion equation [20,21,22,23,24]. The numerical model of imbibition considering the effects of surfactant, which are wettability alteration and IFT, were also established [25,26].…”
Section: Cos Cmentioning
confidence: 99%
“…They showed that imbibition of wetting phase from the fracture into the matrix is proportional to the volume of injected water at low injection rates (filling fracture regime) and proportional to the square root of time at high flow rates (instantly-filled fracture regime). Alshehri et al (2009) investigated the improvement of oil recovery in the presence of gravity when IFT is reduced. The experiments were also conducted on silicon micromodels and it was found that oil recovery improved to about 90% (compared to 74% when gravity had no effect) in a scheme using spontaneous imbibition followed by forced imbibition scheme.…”
Section: Imbibition Experimentsmentioning
confidence: 99%
“…As water injection methods continue to evolve, oilfields are entering periods of high water cut or even ultra-high water cut stages [1][2][3][4][5][6]. This leads to highly dispersed remaining oil, presenting significant challenges for oilfield development [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%